Milestones of evolution of Tuvan Shagaa - Dongak, Svetlana Ch. (The New Research of Tuva, 2015)
Article presents some historic aspects of Tuvan New Year festival Shagaa linked to nomadic household of Tuvans as well as Chinese lunar-solar calendar including the 12-year animal cycle.